2001
DOI: 10.1159/000049715
|View full text |Cite
|
Sign up to set email alerts
|

Breaking Strength of Native and Sutured Trachea

Abstract: Tracheal anastomoses are, even more so than other sutures, often only possible to prepare under tension and thus in danger of breakage. No information is available regarding native tracheae and freshly sutured tracheae. For this reason, our objective was to examine the tensile strength of native tracheae and compare it with freshly sutured specimens. Fresh tracheae were collected from the local slaughterhouse within 30 min of slaughter. With the help of a suitable holding device, 24 fresh tracheae were mounted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 19 publications
1
34
2
Order By: Relevance
“…On the other hand, with the single interrupted suture, there are always individual stitches that are pulled more tightly than others (10). Under mechanical stress these individual stitches are exclusively exposed to the maximum force until the thread breaks or they cut into the tissue beneath (9). Although the continuous suture technique was reported to be superior (9-11), we did not find any statistical difference in air leakage pressure between interrupted and continuous suture patterns.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…On the other hand, with the single interrupted suture, there are always individual stitches that are pulled more tightly than others (10). Under mechanical stress these individual stitches are exclusively exposed to the maximum force until the thread breaks or they cut into the tissue beneath (9). Although the continuous suture technique was reported to be superior (9-11), we did not find any statistical difference in air leakage pressure between interrupted and continuous suture patterns.…”
Section: Discussioncontrasting
confidence: 56%
“…Behrend reported that a continuous suture leads to a homogeneous distribution of energy between the individual loops of the suture's spiral (9). Other reported advantages include reduced likelihood of focal ischaemia, air and watertight seal, and an increase of tensile strength (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These showed that single-stitch sutures were significantly weaker than continuous sutures or sutures performed in mixed technique [14]. In experimental studies, involving the trachea of sheep, Behrend et al [15,16] tested the same three suture techniques as the authors of this study. Various lengths of resection (3, 6 and 9 cm) were observed at intervals of 1, 2, 4, 8 and 24 weeks regarding mechanical stability.…”
Section: Discussionmentioning
confidence: 99%
“…However, limitations exist in interpretation of results secondary to a lack of normative data. Behrend et al established a method of measuring the normative tensile strength of sheep trachea as well as various anastomotic techniques applied to sheep trachea . This model has served as a framework to further define animal trachea characteristics, but is exclusive and species specific.…”
Section: Discussionmentioning
confidence: 99%